2022
DOI: 10.47175/rielsj.v3i2.476
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Students Assessing the Level of Difficulty Test Item on Interest and Motivation in Learning Mathematics

Abstract: According to Item Response Theory, the difficulty level is a characteristic of the test item. The difficulty level of the test items is a characteristic of the test items that are on a scale with the ability level parameter. However, this relationship has not been studied optimally, especially in students' interest and motivation in learning mathematics. This study examines the impact of student involvement in assessing the level of the difficulty test item on interest and motivation in learning mathematics wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Other studies have shown that involving students in the assessment process in the classroom can increase student interest and motivation. The study involved students conducting class assessments (Rukli, 2022).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…Other studies have shown that involving students in the assessment process in the classroom can increase student interest and motivation. The study involved students conducting class assessments (Rukli, 2022).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%